Factors That Influence The Intention To Use Internet Service Provider Lajunet With The Technology Acceptance Model (TAM) Approach - Mashudi; Mahrinasari MS; Roslina (Cita konsultindo, 2026)
This study aims to analyze the factors influencing the intention to use the Internet Service Provider (ISP) LaJUNet using the Technology Acceptance Model (TAM) framework. Although previous literature has extensively applied TAM, a research gap remains regarding how system quality moderates these factors within the context of a local ISP. The primary objective of this research is to examine the effect of Perceived Ease of Use and Perceived Usefulness on the intention to use, moderated by E-System Quality. A quantitative survey approach was employed, collecting data through questionnaires distributed to users familiar with LaJUNet. The findings indicate that perceived ease of use and perceived usefulness significantly influence the intention to use ISP services. However, as a novel contribution, this study reveals that E-System Quality does not moderate the relationship between either perceived ease of use or perceived usefulness and the intention to use. This suggests that while system quality is crucial, enhancing the perceived ease and benefits of a service remains the primary driver of usage intention.